Use of efficient microorganisms in agriculture (Research, Society and Development, 2021)
The interest in the use of microorganisms in agricultural practices has increased significantly in recent years, both in the promotion of plant growth and in the biological control of plant pests and diseases. This literature review work aimed to address information on the use of isolation, multiplication, use and storage methodologies for efficient microorganisms (Effective Microorganisms, EM) in agriculture. These microorganisms have important functions for their hosts, as they have symbiotic interactions with them, and are capable of protecting plants from attack by insects, diseases and herbivorous mammals through the production of toxins. The use of EM in agriculture aims to accelerate the natural composition of organic matter and promote the balance of microbial flora contributing to plant development. EMs are potential substitutes for chemical products, and can thus favor the preservation of the environment. They are collected from fertile forest soils through simple and inexpensive methodologies, consisting of a tool with potential to be used both by family farmers and on a small and large scale. They can be used in different ways, the main ones being in soil, plant, water and animals. The use of EM is an accessible and low-cost technique, in addition to being easy to prepare within the property itself, contributing to the sustainability of agricultural systems.